ChemInform Abstract: Potential and Challenges of Zeolite Chemistry in the Catalytic Conversion of Biomass. Issue 12 (March 2016) - Ennaert, Thijs; Van Aelst, Joost; Dijkmans, Jan; De Clercq, Rik; Schutyser, Wouter; Dusselier, Michiel; Verboekend, Danny; Sels, Bert F.
Abstract: Review: 421 refs.